Multilaboratory Testing of Two-Drug Combinations of Antifungals against Candida albicans, Candida glabrata, and Candida parapsilosis - Chaturvedi, Vishnu (American Society for Microbiology (ASM), 2011)
There are few multilaboratory studies of antifungal combination testing to suggest a format for use in clinical laboratories. In the present study, eight laboratories tested quality control (QC) strain Candida parapsilosis ATCC 22019 and clinical isolates Candida albicans 20533.043, C. albicans 20464.007, Candida glabrata 20205.075, and C. parapsilosis 20580.070. The clinical isolates had relatively high azole and echinocandin MICs. A modified CLSI M27-A3 protocol was used, with 96-well custom-made plates containing checkerboard pairwise combinations of amphotericin B (AMB), anidulafungin (AND), caspofungin (CSP), micafungin (MCF), posaconazole (PSC), and voriconazole (VRC). The endpoints were scored visually and on a spectrophotometer or enzyme-linked immunosorbent assay (ELISA) reader for 50% growth reduction (50% inhibitory concentration [IC(50)]). Combination IC(50)s were used to calculate summation fractional inhibitory concentration indices (FICIs) (ΣFIC) based on the Lowe additivity formula. The results revealed that the IC(50)s of all drug combinations were lower or equal to the IC(50) of individual drugs in the combination. A majority of the ΣFIC values were indifferent (ΣFIC = 0.51 to 2.0), but no antagonism was observed (ΣFIC ≥ 4). Synergistic combinations (ΣFIC ≤ 0.5) were found for AMB-PSC against C. glabrata and for AMB-AND and AMB-CSP against C. parapsilosis by both visual and spectrophotometric readings. Additional synergistic interactions were revealed by either of the two endpoints for AMB-AND, AMB-CSP, AMB-MCF, AMB-PSC, AMB-VRC, AND-PSC, CSP-MCF, and CSP-PSC. The percent agreements among participating laboratories ranged from 37.5% (lowest) for AND-CSP and POS-VOR to 87.5% (highest) for AMB-MCF and AND-CSP. Median ΣFIC values showed a wide dispersion, and interlaboratory agreements were less than 85% in most instances. Additional studies are needed to improve the interlaboratory reproducibility of antifungal combination testing.